Heat conduction analysis in solid with temperature dependent thermal conductivity - Heng, Bin Xun (Nanyang Technological University, 2020)
This report aims to study the effect of changing of parameter of thermal conductivity, K(T) = αT+β on steady heat conduction in two-dimensional solid in rectangular coordinate system. Heat conduction in solids will be examined on an OXY plane. It is found that temperatures in the solution domain of the solid are very sensitive when alpha changes and they are insensitive when beta changes.